Does periodic vehicle inspection reduce car crash injury? Evidence from the Auckland Car Crash Injury Study - Stephanie Blows; Rebecca Q. Ivers; Jennie Connor; Shanthi Ameratunga; Robyn Norton (Elsevier, 2003)
Abstract Objectives:This paper examines the association between periodic motor vehicle inspection and frequent tyre pressure checks, and the risk of car crash injury. Methods:Data were analysed from the Auckland Car Crash Injury Study, a population‐based case‐control study in Auckland, NZ, where vehicles are required to undergo six‐monthly safety inspections. Cases were all cars involved in crashes in which at least one occupant was hospitalised or killed, which represented 571 drivers. Controls were randomly selected cars on Auckland roads (588 drivers). Participants completed a structured interview. Results:Vehicles that did not have a current certificate of inspection had significantly greater odds of being involved in a crash where someone was injured or killed compared with cars that had a current certificate, after adjustment for age, sex, marijuana use, ethnicity and licence type (OR 3.08, 95% CI 1.87-5.05). Vehicles that had not had their tyre pressure checked within the past three months also had significantly greater odds of being involved in a crash, compared with those that had a tyre pressure check, after adjustment for age, sex, ethnicity, seatbelt use, licence type, self‐reported speed and hours per week of driving exposure (OR 1.89, 95% CI 1.16-3.08). Conclusions:This study provides new evidence, using rigorous epidemiological methods and controlling for multiple confounding variables, of an association between periodic vehicle inspections and three‐monthly tyre pressure checks and reduced risk of car crash injury. Discussion:This research suggests that vehicle inspection programs should be continued where they already exist and contributes evidence in support of introducing such programs to other areas.